2007
DOI: 10.1007/s00271-007-0075-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil–water and solute movement under precision irrigation: knowledge gaps for managing sustainable root zones

Abstract: 1Precision irrigation involves the accurate and precise application of water to meet the 2 specific requirements of individual plants or management units and minimize adverse 3 environmental impact. Under precision irrigation applications, water and associated solute 4 movement will vary spatially within the root zone and excess water application will not 5 necessarily result in deep drainage and leaching of salt below the root zone. This paper 6 estimates that 10% of the irrigated land area (producing as much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 22 publications
0
25
0
5
Order By: Relevance
“…Alternatively, scientists and water and environmental managers increasingly use computer models to study the complex processes in the soil (Phogat et al 2000(Phogat et al , 2009Raine et al 2007) to provide management and planning guidance. A wide variety of models exists for simulating water flow and solute transport in the vadose zone.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, scientists and water and environmental managers increasingly use computer models to study the complex processes in the soil (Phogat et al 2000(Phogat et al , 2009Raine et al 2007) to provide management and planning guidance. A wide variety of models exists for simulating water flow and solute transport in the vadose zone.…”
Section: Introductionmentioning
confidence: 99%
“…Precision irrigation is an evolving field with active interest by both industry and academic researchers. It is conceptualized by some researchers as the use of efficient irrigation application systems, whereas others view it as the variable application of irrigation based on predefined maps or sensor feedback [10]. Smith et al [11] suggested that 'precision' involves the accurate determination, quantification of crop water needs and the precise application of the optimal water volume at the required time.…”
Section: Introductionmentioning
confidence: 99%
“…Innovations in irrigation technology usually focus on optimizing timing, wetting patterns, and intensity of irrigation to increase resource use efficiency with the preset assumption of crop root distribution. However, the plasticity of root systems and the interactions between roots and rhizosphere microbes that mediate plant nutrient uptake and soil nutrient cycling have been largely neglected (Raine et al, 2007). Our study tackles this knowledge gap by assessing responses of root traits and rhizosphere processes to moisture and nutrient patterns determined by irrigation strategies in an organic system and provides insights into their relationships with plant nutrient uptake, yield, and soil nutrient cycling.…”
Section: Discussionmentioning
confidence: 99%
“…In agroecosystems, irrigation practices are designed to deliver water to crop roots, but the spatiotemporal dynamics of resource availability are rarely perfectly coupled with plant demand (Howell, 2001). This mismatch arises from limited research on how roots and rhizosphere processes respond to water and nutrient dynamics that are shaped by irrigation methods over space and time (Raine et al, 2007). The neglect of root and rhizosphere interactions during the implementation of new irrigation practices, especially when management changes are made based on experience or external reasons, can lead to inefficient use of costly inputs and damaging losses into the environment (Vázquez et al, 2006;Thompson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%